Redefining Value : The Future of Corporate Sustainability Ratings - White, Allen L (World Bank, Washington, DC, 2014)
Corporate sustainability ratings are a potentially powerful but still underused tool for building a competitive, socially purposeful, and financially sound enterprise. In a globalizing world replete with business opportunities and risk, corporate boards continually need to reappraise what constitutes good governance. Traditional board duties pertaining to strategic oversight, executive compensation, and financial auditing will remain integral for the foreseeable future. But these alone will not suffice in a time when the prosperity of companies is inextricably linked to issues such as reputation, brands, supply chain management, quality and quantity of human and intellectual capital, protection of human and labor rights, and climate change. Such emergent issues are part of a historical moment in which the role of companies in fostering societal and ecological well-being at the global, national, and local levels is under increasing scrutiny. These are conditions that fuel intensifying public discourse concerning corporate social responsibility, sustainable capitalism, shared value creation, and other linked concepts that challenge the conventional wisdom that positions shareholder value as the paramount measure of company success. Indeed, sustainability is not new to the two common definitions of corporate governance: (i) the actual behavioral patterns of corporations in terms of efficiency, growth, financial structure, and other attributes; and (ii) the normative framework within which firms operate in terms of legal systems, financial markets, and labor markets.